Molecular Basis for the Cation Selectivity of Salmonella typhimurium Melibiose Permease. Issue 12 (30th June 2022) - Katsube, Satoshi; Liang, Ruibin; Amin, Anowarul; Hariharan, Parameswaran; Guan, Lan
Graphical abstract: Highlights: Cation selectivity is an important attribute of cation-coupled symporters. Novel insights into the molecular basis for Na + and Li + selectivity in MelB. Li + binding only requires a subset of residues in the Na + binding site. The charge balance of MelBSt cation-binding site plays an important role in the protein stability. Our findings can be extended to other human cation-coupled transporters. Abstract: Cation selectivity and coupling are important attributes of cation-coupled symporters. Salmonella typhimurium melibiose permease (MelBSt ) catalyzes the co-transport of galactosides with cations (H +, Li +, or Na + ). 3-D crystal structures of MelBSt have revealed the molecular recognition for sugar substrates, but the cation binding and coupling mechanisms have not been defined to atomic levels. In its human homolog MFSD2A, a lethal mutation was mapped at its Na + -binding pocket; however, none of the structures in this subfamily resolved its cation binding. In this study, molecular dynamics simulations reveal the binding interactions of Na + and Li + with MelBSt . Interestingly, Thr121, the lethal mutation position in MFSD2A, forms stable interaction with Na + but is at a distance from Li + . Most mutations among 11 single-site Thr121 mutants of MelBSt exhibited little effects on the galactoside binding, but largely altered the cation selectivity with severe inhibitions on Na + binding. Few mutants (Pro and Ala) completely lost the Na + binding and Na + -coupled transport, but their Li + or H + modes of activity were largely retained. It can be concluded that Thr121 is necessary for Na + binding, but not required for the binding of H + or Li +, so a subset of the Na + -binding pocket is enough for Li + binding. In addition, the protein stability for some mutants can be only retained in the presence of Li +, but not by Na + due to the lack of affinity. This finding, together with other identified thermostable mutants, supports that the charge balance of the cation-binding site plays an important role in MelBSt protein stability.